A genre analysis of master dissertation abstracts written by English native speakers and Tunisian EFL learners: Pedagogical considerations - Hamdi, Sondes (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
Despite the growing interest in genre analysis, on the one hand, and the continuous concern with academic writing, on the other, very little has been done on the move structure of abstracts in Linguistics Master dissertations written by native speakers and non-native speakers of English (Al-Khasawneh, 2017). In the same vein, no single cross-linguistic study has investigated variations in the move structure of abstracts in dissertations written by English native speakers and Tunisian EFL learners. This paper is a response to this need. It purports to analyze the move structure of abstracts in Linguistics MA dissertations written by English native speakers and Tunisian EFL learners, within the theoretical framework of Hyland’s five-move model (2000). Twelve abstracts were selected for this study: Six abstracts were written by Tunisian EFL MA students at the Institut Supérieur des Langues à Tunis (ISLT, Tunisia) and six abstracts were written by English native speakers. The native speakers’ abstracts were randomly chosen from the Brigham Young University website for Linguistics Theses and Dissertations. The EFL learners’ abstracts were randomly chosen from the ISLT library. The findings suggest that the Purpose move, the Method use and the Product move are frequent in both corpora. However, only one English abstract in 6 contains the Conclusion move, whereas 4 EFL abstracts in 6 contain the Conclusion move. Both corpora contain the Introduction move, with equal frequency (4 in 6 for both corpora). Pedagogical considerations are highlighted for EFL teachers in order to ensure an efficient abstract teaching. It is argued that this study represents a contribution to the field of academic writing and genre analysis.